Pengembangan Realistik Sebagai Pilihan dalam Peningkatkan Pemahaman Konsep Pengujian Hipotesis - Susie Harini (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2015)
By identifying those problems of development, the researcher was eager to develop model, which was able to improve students’ understanding concept toward the material about testing the hypothesis. In addition, this model should be able to develop students’ participation in develop activities. One of the teaching develop models that can help students in understanding the concept of testing the hypothesis is Realistic develop.